Aturan Hukum Sebelum Islam - Wihda Yanuar Firdaus; Siti Nurjanah; Siti Zulaikha; Agus Hermanto (Moral : Jurnal kajian Pendidikan Islam, 2025)
Understanding the legal system before the arrival of Islam is essential to trace the social, cultural, and spiritual transformation of society, especially Arab. The pre-Islamic legal system, known as the Jahiliyah legal sistem, reflects the social reality of the time and is the main comparison for the radical changes brought by Islam. This study aims to provide an explanation of the forms of law, their characteristics, and sources of law that applied in the pre-Islamic period (Jahiliyah) before the arrival of the Prophet Muhammad SAW. This study uses a qualitative approach with a historical descriptive method. Based on the results of an in-depth study of the pre-Islamic legal sistem (Jahiliyah), it can be concluded that the law in the pre-Islamic period was unstructured, particularistic, and heavily influenced by customary power and tribal dominance.